Global survivors or national identity: exploring family language policy in Indonesian families - Oktavia, Feliani (Universitas Negeri Semarang, 2024)
This article discusses the family language policy incorporating language ideology towards Bahasa Indonesia and English which serves as the driving force of Indonesian parents' language practice and efforts to improve their children's linguistic competence. Indonesian families still hold Bahasa Indonesia in high regard and they are aware of the importance of mastering English in order to survive in the global economy and society. Their ideologies towards their national language and English are revealed through the use of Bahasa Indonesia as their main language practice at home and their efforts to introduce English to their children at a very young age including sending them to bilingual or language schools. The findings of this study will guide other families in their language practice, particularly how to support their children's language development. Further investigation is needed to discover the family language in wider scope or different contexts which may lead to other possible findings